2008
DOI: 10.4161/psb.3.10.6247
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic acid-mediated salt signaling in seed germination

Abstract: salinity delays seed germination by reducing GA biosynthesis. 7 ABA is a major plant growth hormone mediating plant responses to high salinity, suggesting that the salt effects on seed germination would depends on this growth hormone. We observed that the GA synthetic enzyme gene GA3ox1 is significantly repressed by high salinity. In particular, the salt repression of GA3ox1 is independent of ABA. The GA3ox1 transcription is efficiently repressed by high salinity even in the ABA-deficient aba3-1 mutant to a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Seed germination can be delayed under unfavourable environmental conditions such as high salinity (Kim and Park, 2008). It has been shown that 100 m m and 150 m m NaCl are permissive and restrictive conditions, respectively, for Arabidopsis seed germination (Saleki et al.…”
Section: Resultsmentioning
confidence: 99%
“…Seed germination can be delayed under unfavourable environmental conditions such as high salinity (Kim and Park, 2008). It has been shown that 100 m m and 150 m m NaCl are permissive and restrictive conditions, respectively, for Arabidopsis seed germination (Saleki et al.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kim et al [10] indicated that 13 members of the NAC domain proteins from Arabidopsis thaliana and 6 from rice were membrane associated transcription factors. However, to the knowledge, NTM1, NTL8, and NTL11 are the only NAC membrane transcription factors whose physiological roles have been studied in detail [8,[10][11][12]. Therefore, exploring the biological role of novel NAC MTFs from other species is required for better understanding of the mechanisms governing their diverse functions.…”
Section: Introductionmentioning
confidence: 97%
“…Salinity is one of the major abiotic stresses that adversely affect crop productivity and quality ( Munns, 2002 ). It was reported that salt stress not only delayed the germination process, reduced the germination rate, but also inhibited the formation of plant seedling after germination ( Kim and Park, 2008 ; Lee et al, 2010 ). Plants have a complex and sophisticated network to antagonize the seed germination inhibition caused by salt stress and many plant hormones and signaling molecules are involved in the process ( Achard et al, 2006 ; Tanou et al, 2009 ; Mur et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have a complex and sophisticated network to antagonize the seed germination inhibition caused by salt stress and many plant hormones and signaling molecules are involved in the process ( Achard et al, 2006 ; Tanou et al, 2009 ; Mur et al, 2013 ). The previous researchers proved that the small signaling molecules ABA, GA, SA, NO, and ETH were all directly involved in the regulation of seed germination inhibition or promotion under salt stress ( Gniazdowska et al, 2007 ; Kim and Park, 2008 ; Lee et al, 2010 ; Arc et al, 2013a , b ; Jiang et al, 2013 ; Lin et al, 2013a ). Ethylene was proposed to release the impaired seed germination and seedling growth through crosstalk with ABA, ROS, and NO during plant response to stress conditions ( Linkies et al, 2009 ; Asensi-Fabado et al, 2012 ; Lin et al, 2012 ; Arc et al, 2013b ).…”
Section: Introductionmentioning
confidence: 99%